Pictionary as a didactic tool to teach english language vocabulary to Pre K Students - Pavón, Junieth; Quiroz, Saúl (Panamá : UDELAS, 2019)
The aim of this project is to find out that Pictionary is a usefui didactic technique for teaching English vocabulary in Kindergarten students of Centro Educativo Tesoros Divinos ,San miguelito morning schift
Incluye Dedication Acknowledgments General Content Introduction CHAPTER: I. THE ORETICALFRAMEWORK 1.1 Theoretical Background of the Proyect 1.2 Diagnosis of the Current Situation 1.3. Justification 1.4. General objectives 1.5 Duration 1.6 Beneficiaries 1.6.1. Direct 1.6.2. Indirect 1.7 Physical Location 1.8 Institucional Framework of the Proyect CHAPTER II THEORETICAL FOUNDATION 2.1 Definitions and Theoretical Foundation 2.1.1. importance of vocabulay 2.1.2. Assocition with pictures 2.2 intervention proposal 2.2.1. Litte of the proposal 2.2.2. Presentation 2.2.3. Justification 2.2.4. Objectives 2.2.5. Methodology 2.2..6. Activity with pictionary 2.2.7. Activities evaluation 2.3. Organizational and proyect management structure 2.4 Operational specification of activities and tasks to be performed 2.5. Products 2.6. Proyect delivery schedule 2.7 Budget CHAPTER III. ANALYSIS OF RESULTS CONCLUSIONES RECOMENDACIONES BIBLIOGRAFÍA REFERENCES
Incluye Contenido General
La entrega del documento es un requisito fundamental para optar por el título de Bachelor's Degree in English Language Teaching
Incluye Bibliografía
No se presta a domicilio No se presta para sacar fotocopia
Keywords: PEDAGOGÍA; ENSEÑANZA; INGLÉS; ENSEÑANZA; DEGREE WORK TO ACHIEVE THE BACHELOR'S DEGREE IN ENGLISH LANGUAGE TEACHING; CENTRO EDUCATIVO TESOROS DIVINOS, SAN MIGUELITO